Neoangiogenesis and microvascular density in myelodysplastic syndrome : a single center experience - Škrtić, Anita (Array, 2019)
Angiogenesis has a significant part in the pathogenesis of hematological malignancies, such as leukemia and myelodysplastic syndromes (MDS). We evaluated the relationship between morphometric, morphological and clinical features of MDS. Blood vessels of 31 newly diagnosed MDS bone marrow biopsies were immunohistochemically analyzed using CD34 and compared with 8 controls and 13 chronic myelomonocytic leukemias (CMML). MDS were categorized into three risk groups: low-, intermediate- and high-risk MDS. Microvascular density (MVD) and major and minor axis length were analyzed using digital image analysis. Overall, MDS had significantly higher MVD and lower minor axis values than the control group and CMML. High-risk MDS had significantly higher MVD compared to the controls, while all MDS risk groups had lower minor axis values than the control group. Increased minor and major axis values were prognostic predictors of shorter overall survival in all MDS risk groups and CMML patients. In conclusion, angiogenesis presents one of the essential factors in MDS pathogenesis and progression characterized by descriptive marrow microvascular network transformation. The size-related features are powerful indicators of survival in MDS patients.